IMeta progress and acknowledgment of reviewers in 2022. Issue 1 (13th February 2023) - Liu, Yong‐Xin; Shi, Chun‐Lin; Ma, Tengfei; Ding, Wubin; Li, Danyi; Chen, Tong; Fu, Jingyuan; Liu, Shuang‐Jiang
Abstract : Milestones of the first year of iMeta. iMeta is an open‐access Wiley partner journal launched by iMeta Science Society consisting of worldwide scientists in bioinformatics and metagenomics. In 2022, iMeta released four issues, including 60 publications with a total of 340 citations. iMeta has been indexed in several databases, including Google Scholar, Crossref, CNKI, Dimensions, PubMed (partial), DOAJ, and Scopus. Thanks to the editorial board members and reviewers for their contributions to the iMeta in 2022.